Problematika Pembelajaran Mata Kuliah Berbahasa Arab Via daring di Masa Pandemi covid-19 (Studi pada Mahasiswa Pendidikan Bahasa Arab (PBA-FAI) UMI Makassar) - Hafid, Wahyudin; Ilyas Thahir (Shaut al Arabiyyah, 2023)
Online learning is an inevitable choice for any educational institution during the outbreak of Covid-19 so that the teaching and learning process can continue where teachers and students can still fulfill their obligations. However, in reality, online learning that utilizes internet technology leaves many problems for lecturers and students and greatly affects learning outcomes. This study aims to describe the problems faced by lecturers and students during online learning in Arabic courses at the Arabic Language Education (PBA) Study Program, Faculty of Islamic Religion, UMI Makassar.Methodologically, this research is a descriptive qualitative research that seeks to describe the phenomena that occur in the field as they are by using research instruments in the form of; observation, structured interviews and documentation with a population of 9 lecturers and 213 students of PBA UMI Makassar using Simple Random Sampling from the population. The research data was processed using the Miles and Huberman method in the form of data collecting, data reduction, data display, and verification and then drawing conclusions.The results of this study indicate that lecturers and students of PBA UMI Makassar experience various obstacles and learning barriers during online lectures. The problems and obstacles are divided into two, namely: (1) technical obstacles in the form of the complexity of frequently used applications, inadequate availability of networks and electronic devices and the ability of students to prepare data quotas and family economic factors. (2) non-technical obstacles or learning problems. itself which includes; difficulty understanding lecture material, unavailability of online teaching materials, non-variative teaching methods, barriers to communication and interaction between lecturers and students as well as issues of discipline, class attendance and mastery. Although it is recognized that online learning also provides several advantages and advantages, especially in terms of time and cost efficiency for both lecturers and students.This study recommends several things, namely; improvement of the network system that is evenly distributed in all regions of Indonesia to facilitate internet access, provision of learning tools in the form of more actual learning facilities and materials, assistance and provision of cheaper internet quotas for students.